2011 IEEE International Conference on Systems, Man, and Cybernetics 2011
DOI: 10.1109/icsmc.2011.6083811
|View full text |Cite
|
Sign up to set email alerts
|

Shared control for road departure prevention

Abstract: A driving simulator experiment is presented investigating different road departure prevention (RDP) setups. To induce the risk of road departure, thirty test drivers were asked to avoid a pylon-confined area (obstacle) while keeping the vehicle within the road limits. The RDP system intervened by applying a haptic-feedback (i.e., haptic shared control) and/or correcting the steering angle (i.e., drive-by-wire (DBW) input-mixing shared control) in the event that a vehicle road departure was likely to occur. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Two studies [48], [66] found that guidance systems supporting lane keeping resulted in more crashes with obstacles compared to a no guidance condition, when these obstacles were placed in the centre of the lane, because the guidance did not recognize these obstacles. Conversely, Brandt et al [41] showed a decrease in collisions when combining guidance and warning systems into a single haptic system.…”
Section: D) Signalmentioning
confidence: 97%
“…Two studies [48], [66] found that guidance systems supporting lane keeping resulted in more crashes with obstacles compared to a no guidance condition, when these obstacles were placed in the centre of the lane, because the guidance did not recognize these obstacles. Conversely, Brandt et al [41] showed a decrease in collisions when combining guidance and warning systems into a single haptic system.…”
Section: D) Signalmentioning
confidence: 97%
“…According to interviews after the experiment, several drivers were, in fact, frustrated by experiencing contradictory guidance. Katzourakis et al (2011) found a similar misconception for an emergency maneuver by a driver assistance system with shared control for road departure prevention.…”
Section: Discussionmentioning
confidence: 87%
“…Many works on haptic shared control have focused on driver assistance in relatively peaceful traffic conditions, such as lane following (Griffiths & Gillespie, 2005), curve negotiation (Forsyth & MacLean, 2006;Mulder, Abbink, & Boer, 2008), voluntary lane changes (Nishimura, Wada, & Sugiyama, 2013;Tsoi, Mulder, & Abbink, 2010), and parking (Hirokawa, Uesugi, Furugori, Kitagawa, & Suzuki, 2014). Additionally, the idea of haptic shared control has been expanded and applied to emergency evasive maneuvers (Della Penna, van Paassen, Mulder, Abbink, & Mulder, 2010;Itoh, Horikome, & Inagaki, 2013), road departure prevention (Katzourakis et al, 2011), and blind-spot collision prevention, which is so-called protection (Itoh & Inagaki, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Advanced driver assistance systems (ADAS) can help a driver to perform the driving task and thus improve the road traffic safety [1], [2]. On the one side systems that only warn the driver in case of an emergency, e.g.…”
Section: Introductionmentioning
confidence: 99%